If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -2 = 61 Reorder the terms: -2 + 7y = 61 Solving -2 + 7y = 61 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 7y = 61 + 2 Combine like terms: -2 + 2 = 0 0 + 7y = 61 + 2 7y = 61 + 2 Combine like terms: 61 + 2 = 63 7y = 63 Divide each side by '7'. y = 9 Simplifying y = 9
| (x-73)+x+67= | | 2y-4+y+9=2y-4+4y+11 | | 3(p+2)+4=5p-2(p+6) | | -r^2-12r+45= | | 6b^4(5b+4b^3)= | | -r^2-12+45= | | 6x=20-8 | | 10+6cos(0.5x)=8 | | 5-2(x+5)=-4x-35 | | -3(4t-2)+4t=8t-7 | | m+6+2m=21 | | 10x-8=163-9x | | 30=-6(x-1)+18 | | x^4-3x-18=0 | | -1x=4.5 | | -2x-16=x+8 | | 6x^2-4x+2=6x^2-12x+x | | 6-6m-3=9 | | 4(f-4)=4(f+6) | | -4-c=-8 | | in(x+5)=3 | | 84=6+6p | | X(x+8)-8=x^2+3x+1 | | 4x-6-8=4 | | 3q+10=37 | | 80=6v+2 | | 2=5+3x-3 | | -8x+1=1-5x-2 | | 12-2(x+5)=27+3x | | y-3x+2y=-8 | | -5x+8x=-12 | | 2(x-4)(x+10)=0 |